Perilaku Tokoh Protagonis dan Antagonis pada Naskah Drama ”Bila Malam Bertambah Malam” Karya Putu Wijaya - Apadu, Rahman; Arsadi, Nurlena; Bagtayan, Zilfa Achmad (Jurnal Bahasa, Sastra, dan Budaya, 2025)
Drama script is a text that contains dialogue with descriptions of the characters in it. This study aims to describe (a) the behavior of the protagonist (b) the behavior of the antagonist and (c) its implications in learning literature in schools. A descriptive qualitative approach is utilized. Using words or images to describe the phenomena of the actions of the existing protagonist and antagonist characters. Characters' actions in passages from Putu Wijaya's "Bila Malam Bertambah Malam" (a play) and classroom instruction in literature served as the basis for the study. Data collection techniques were taking notes, reading repeatedly, and observing at school. The data analysis technique used qualitative descriptive, by studying the drama script of the protagonist and antagonist characters and literature learning in schools. The results of the study showed that (1) the behavior of the protagonist depicted in the drama script "Bila Malam Bertambah Malam" in the character Nyoman has a helpful, patient, sincere and good behavior (2) the behavior of the antagonist in the character Gusti Biang has a rude, arrogant, inhumane, and immoral behavior. In addition, in its implications for literature learning in schools, it can be done using the literature teaching method.